Implementation of Technology-Based Learning Media in the Classroom Using Edpuzzle in the Basics of Accounting Subject for Class X AK1 Accounting and Finance Department at SMKN 1 Sampit in 2025 - Ifan Julianta; Norlela Norlela; Siti Halimah; Izzatil Husna; Rifdah Maimunah; Najwatu Tsania (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The purpose of this study is to identify the effectiveness of the use of interactive video-based learning media Edpuzzle in the subject of Accounting Basics. The population in this study involved all grade X students of the Accounting and Finance Department of SMKN 1 Sampit, with a research sample of 5 grade X AK1 students selected using saturated sampling techniques. Data collection was obtained based on learning outcome tests before and after the use of Edpuzzle (pretest and posttest). The data analysis technique used was a paired sample t-test to determine the average difference in student learning outcomes before and after treatment. Data analysis with a significance level of 5% (? = 0.05) has a 95% confidence interval. The analysis results prove that the average value of student learning outcomes after using Edpuzzle is higher than before using Edpuzzle, with an effectiveness score of 85%. The t-test results produce a calculated t score > t table. Thus, it can be confirmed that there is a drastic change in the educational achievement of the subjects before compared to after the treatment of using Edpuzzle media. The 95% confidence interval shows that the increase in learning outcomes is in the range of 80%–90%, which indicates that the use of Edpuzzle has a positive and consistent impact on student understanding. Based on these results, it can be concluded that Edpuzzle-based learning media is successfully applied in learning Accounting Basics because it is able to optimize learning outcomes, engagement, and student motivation.